2022
DOI: 10.3389/fpsyt.2022.919191
|View full text |Cite|
|
Sign up to set email alerts
|

Epistemic trust and personality functioning mediate the association between adverse childhood experiences and posttraumatic stress disorder and complex posttraumatic stress disorder in adulthood

Abstract: BackgroundAdverse childhood experiences (ACEs) are associated with posttraumatic and complex posttraumatic stress disorder symptoms in adulthood (PTSD/cPTSD), as well as reduced epistemic trust (trust in the authenticity and personal relevance of interpersonally transmitted information) and impaired personality functioning. The present work aims to investigate the predictive value of epistemic trust—the capacity for social learning—on the mediating effect of personality functioning in the association of ACEs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 60 publications
4
28
0
Order By: Relevance
“…In their longitudinal twin study on 2,200 children, the authors found lower mentalizing capacities in individuals who had experienced problems in peer relationships, especially after becoming a victim of bullying, acting as a bully, or switching between a bully and a victim role. Epistemic disruption has furthermore been shown to partially mediate the relationship between maltreatment and PTSD as well as complex PTSD symptomatology [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their longitudinal twin study on 2,200 children, the authors found lower mentalizing capacities in individuals who had experienced problems in peer relationships, especially after becoming a victim of bullying, acting as a bully, or switching between a bully and a victim role. Epistemic disruption has furthermore been shown to partially mediate the relationship between maltreatment and PTSD as well as complex PTSD symptomatology [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A constantly growing body of evidence has documented the detrimental effect of Adverse Childhood Experiences (ACEs) on physical and mental health in adulthood [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Typically, ACEs include various types of physical and/or emotional ill-treatment, sexual abuse, neglect, and commercial or other exploitation experienced by children under 18 years of age [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This constant state of strong suspiciousness toward others is the core of borderline psychopathology (Fonagy et al, 2015). Although there is still little research on ET development, some evidence supports this perspective (Campbell et al, 2021;Kampling et al, 2022). Both Corriveau and Colleagues (2009) and Venta (2020) empirically investigated the role of attachment on the possibility of the child accepting incoming socially transmitted knowledge.…”
Section: From Epistemic Vigilance To Epistemic Trust: How Does Et Dev...mentioning
confidence: 99%
“…ET is a recent concept, and to our knowledge, only a few studies have operationalized the concept beyond clinical reflection (Campbell et al, 2021;Fonagy & Allison, 2014;Kampling et al, 2022;Orme et al, 2019;) and explored its influence on the quality of interpersonal exchanges. Also, some authors tried to develop specific measurements for this construct, such as the Epistemic Trust Assessment (Schröder-Pfeifer et al, 2018 and the Epistemic Trust Mistrust Credulity Questionnaire (Campbell et al, 2021).…”
Section: From Epistemic To Interpersonal Trustmentioning
confidence: 99%
“…University students must continuously evaluate the credibility of information from various sources to make informed decisions and succeed academically. Building epistemic trust enables students to engage critically with academic materials, seek guidance from fellow students and mentors and participate actively in classroom discussions (Campbell et al, 2021;Kampling et al, 2022;Riedl et al, 2023). A welldeveloped sense of epistemic trust is a prerequisite for a supportive learning environment, encouraging knowledge sharing and cooperative learning.…”
Section: Introductionmentioning
confidence: 99%